Determining the optimum shape and orientation of a greenhouse on the basis of total radiation (2011)
Greenhouse is a feasible option for sustainable crop production in the regions of adverse climatic conditions. For a successful greenhouse design, the selection of shape and orientation is of paramount importance. In this study, three most commonly used single span shapes of greenhouses namely even-span, uneven-span and vinery type have been selected for comparison. The length, width and height (at the center) are kept same for all the selected shapes. The relevance of this paper was to develop a thermal model using MATLAB program for computing transmitted total solar radiation (beam, diffused and ground reflected) at each hour, for each month and at any latitude for the selected geometry greenhouses (through each wall, inclined surfaces and roofs) for both east-west and north-south orientation. The computed transmitted solar radiation is then introduced into another thermal model that is developed using MATLAB program to compute hourly inside air temperature for each shape and orientation. Statistical validation is carried out for the former model using solar radiation data for horizontal surface at (28°35'N and 77° 12'E),New Delhi, India and (19° 07'N and 72°51'E),Mumbai, India. At 19°N latitude, uneven-span shape greenhouse receives 10% more yearly average solar radiation as compared to even-span shape greenhouse whereas vinery shape to receives 12%less yearly average solar radiation as compared to even-span shape. Similarly, at 28°N latitude, unevenspan shape to receives 8% more average radiation as compared to even-span shape whereas vinery shape receives 10% less yearly average solar radiation as compared to even-span shape. Results above show that east-west orientation of uneven-span solar greenhouse is the best suited during each month for both analyzed latitudes. The developed model is very simple and has provided understanding to climate control process inside the greenhouse.